Peran Profitabilitas dalam Memediasi Pengaruh Good Corporate Governance (GCG) dan Corporate Social Responsibility (CSR) terhadap Nilai Perusahaan di Indeks LQ45 (2019 – 2023) - Hartanto, Ignatius Edbert; Trimurti, Christimulia Purnama; Adinegara, Gusti Ngurah Joko; Nainggolan, Gilbert (Universitas Batanghari Jambi, 2025)
This study examines the function of profitability in mediating the influence of corporate governance, and corporate social responsibility on company value in companies listed on the LQ45 Index during the period 2019 - 2023. The structural equation modeling (SEM) analysis method based on partial least square (PLS). The results of this study indicate that Good Corporate Governance (GCG) and Corporate Social Responsibility (CSR) have a significant positive effect on company value. GCG assessed through the ratio of independent commissioners and the size of the audit committee shows a significant positive impact on profitability, while CSR does not show a significant effect. Profitability is proven to function as a mediator in the relationship between GCG and company value, but does not function as a mediator in the relationship between CSR and company value. In addition, this study found that efficient GCG implementation can increase company value both directly and through increased profitability, while the effect of CSR on company value is more focused on creating long-term value through increasing stakeholder reputation and loyalty.